THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF NAFISA PRODUCTION EMPLOYEES IN SURABAYA - Erni Hariyanie; Achmad Daengs GS; Rina Dewi; Bambang Karnain; Sugiharto; Enny Istanti (PT. Mawadaku Sukses Solusindo, 2023)
This research was motivated by a decline in performance at Nafisa Production in Surabaya. Because Human Resources are central figures in organizations and companies. In order for management activities to run well, the company must have employees who are knowledgeable and highly skilled and strive to manage the company as optimally as possible so that employee performance increases. The more employees have high performance, the company's overall productivity will increase so that the company will be able to survive in global competition. The purpose of this research is to determine the influence of motivation and work environment on employee performance.Using the questionnaire method by distributing questionnaires to 35 Nafisa Production employee respondents in Surabaya. Based on data analysis and simultaneous hypothesis testing in this research, it can be seen that motivation (X1) and work environment (X2) simultaneously influence employee performance (Y), this can be proven by the calculated F value (23.380) > F table (2.034 ). Meanwhile, the R multiple value of 0.771 shows that the closeness of the relationship between the independent variable and the dependent variable is 77.10%. Meanwhile, the coefficient of multiple determination is 0.594, which means that all independent variables can explain employee performance (Y) by 59.40%. Partially, motivation influences the performance of Nafisa Production employees, this can be seen from the calculated t value, which is greater than motivation (X1) of 2.918 compared to the work environment variable which is only 2.918. Thus it is concluded that motivation and work environment have a significant influence on the performance of NAFISA Production Surabaya employees.